Edukasi Perencanaan Karir sebagai Upaya Pengembangan Diri Siswa Siswi Kelas IX MTs Sirojul Af’idah Desa Ciherang, Gunungsari, Kabupaten Serang: Penelitian - Elmi Nurvianti; Fitriani Yuniar; Sahrul Aziz; Afrida Gian Fitriani; Obi Erdiansyah; Ahmad Abiduri Dimyati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Early career planning is an essential aspect to ensure that students have clear direction and goals in both education and future employment. This study aims to enhance the understanding of ninth-grade students at MTs Sirojul Af’idah regarding the importance of planning their careers based on potential, interests, and aspirations. A qualitative method was applied through observation of students’ understanding before and after the career education activities, which were carried out using lectures and interactive discussions. The findings indicate an increase in students’ awareness of the urgency of designing career plans aligned with their talents and life goals. Furthermore, the program motivated students to pursue higher education at relevant levels, improved their communication skills, and encouraged the exploration of new interests. Despite challenges such as limited time and the absence of continuous mentoring, this educational activity had a positive impact on the students. Therefore, it is recommended that structured career counseling programs be implemented to further support students in effectively planning their future.